Fourth graders' performance on a state-mandated assessment involving two different measures of reading comprehension - Spear-Swerling, Louise (Reading Psychology, 2004)
This study examined fourth graders' performance on two reading comprehension measures, involving a question-answering format and a cloze format, which were part of a state-mandated assessment. Word-level reading skills and oral language comprehension were important to success on both formats, but word accuracy had a stronger relationship to the cloze than to the question-answering measure. Language comprehension related strongly to both formats. The cognitive profiles associated with poor reading comprehension varied, but most often involved a specific difficulty in accuracy of pseudoword decoding. The results suggest that test format should be considered in interpreting reading comprehension performance and underscore the need to assess specific component abilities in reading.
31 citations (Crossref) [2023-10-31] Citation Key Alias: pop00053 tex.type: [object Object]
Keywords: dept.sed